Assessment of Landscape Conflicts in Motorway Planning, NE Hungary - Mészáros Szilvia; Gergely Attila; Illyés Zsuzsanna (Journal of Environmental Geography, 2018)
Field surveys are essential in the Hungarian motorway planning process so that it would be possible to assess their impacts on the landscape, since the available databases are insufficient in respect of listing all the valuable elements of the landscape. The aims of the research are to analyse the impacts of the planned M30 Motorway (located in north-eastern Hungary) on the landscape, to enumerate the cultural and natural valuable elements of the landscape near and within the area to be expropriated, to explore the possibilities of their protection and to outline the possible land use conflicts likely to arise after the implementation of the motorway. The main sources used for the research were: landscape, green space management and environmental protection studies made for the modification of the affected settlements’ urban plans, field surveys alongside the entire track, and existing environmental databases. In the case of M30 motorway, the chosen corridor was mostly acceptable in the sections where the motorway track leads along the track of the existing Main Road 3, because it is fitted to an existing linear artificial landscape element, it is basically on the border of two natural micro-regions and can also fit into the existing land use structure. Nevertheless, it is not considered to be the best choice in places where it separates vineyards from vine cellars, where it is located within 50 meters from residential areas or where it passes through small plot vineyards or horticultural areas instead of the arable lands of the nearby plain.